Process Innovation in Local Governments: an empirical study of continuous improvement effort - Suárez-Barraza, Manuel Francisco (Review of Business Management, 2013)
This article seeks to explore and understand how applies the process innovation (PI) in Spanish local administrations over the years. Therefore, we conducted a qualitative study with a case study research method of four Spanish municipalities, using the following strategies for data gathering: direct observation, participatory observation, document analysis, and semi-structures in-depth interviews. Theories or schools of thought in which the study is based Public Management and Operations Management in the field of Process Innovation. The findings indicate that the implementation of the PI address in local governments is presented through a series of evolutionary stages and improvement activities. The impact in the different processes and public services has been beneficial in terms of internal performance and satisfaction to the citizen. Therefore, when such public institutions have had the will and the commitment of politicians and senior technicians to innovate their work processes, that effort has been the practice of steadily over the years. It is one of the first studies to explore the application of Process Innovation in public management of local governments.